Outcomes of CSF spectrophotometry in cases of suspected subarachnoid haemorrhage with negative CT: two years retrospective review in a Birmingham hospital. (4th March 2017) - Bakr, A.; Silva, D.; Cramb, R.; Flint, G.; Foroughi, M.
Abstract: Aim: The aim of this study was to evaluate the adherence to current guidelines for the investigation of suspected subarachnoid haemorrhage and the prevalence and outcome of computed tomography (CT)-negative aneurysmal subarachnoid haemorrhage. Design: A retrospective review in a single large tertiary referral centre. Subjects: A total of 796 patients, aged 16–90 years, who underwent lumbar puncture (LP) for suspected subarachnoid haemorrhage (SAH) following a negative or equivocal CT scan between January 2012 and November 2013 (23 months). Methods: Xanthochromia reports were obtained using the hospital's department of biochemistry database and clinical data for these patients were reviewed using patient notes. Results: Of 796 CSF reports reviewed, 728 (91%) were negative for xanthochromia, 31 (4%) were positive and 37 (5%) were equivocal. Only 2 out of the 31 patients with positive spectrophotometry results were subsequently found to have an underlying aneurysm on CT angiography. A further 9 out of these 31 patients underwent digital subtraction angiography, with no cerebral aneurysms being detected. Amongst the 37 patients with equivocal xanthochromia reports, 13 underwent CT angiography and only 1 cerebral aneurysm was detected. Conclusions: In patients with clinically suspected SAH but who have negative or questionable CT findings, CSF analysis is likely to be negative in the vast majority of cases, which was 91% in our series. In patients yielding positive or equivocal CSF results the likelihood of an aneurysm being detected is low, amounting to three out of 68 or approximately one in 23 (approximately 4%). Overall in suspected SAH cases where CT scan has been negative, the rate for the detection of cerebral aneurysm is three out of 796 cases (0.4%).